Book review: Post neo-liberal economics - Jahangir, Junaid (My University, 2022)
The book, edited by Edward Fullbrook and Jamie Morgan, is a collection of articles published in the Real-World Economics Review (Vol. 96, 2021). The book assembles 15 essays from leading heterodox economists who offer their vision of economics beyond economic theory and the current hegemonic system of neoliberalism. This collection of essays provides an insight into ideas that could offer an alternative to the standard principles of economics in the Mankiw et al. (2020a, 2020b) textbook (and its variant versions) which is singled out for its global reach and because it forms the basis of the critique of several heterodox economists (Davis et al., 2019; Goodwin, 2014). This review focuses on salient ideas that could be presented to ECON 101 students. Thus, the key ideas presented in Post Neo-Liberal Economics, which, by the way, I fully endorse and recommend, are systematically delineated below.
Keywords: post-neoliberal economics; interdisciplinary approaches